Report on WHO meeting on immunization in older adults: Geneva, Switzerland, 22–23 March 2017. Issue 7 (8th February 2018) - Teresa Aguado, M.; Barratt, Jane; Beard, John R.; Blomberg, Bonnie B.; Chen, Wilbur H.; Hickling, Julian; Hyde, Terri B.; Jit, Mark; Jones, Rebecca; Poland, Gregory A.; Friede, Martin; Ortiz, Justin R.
Abstract: Many industrialized countries have implemented routine immunization policies for older adults, but similar strategies have not been widely implemented in low- and middle-income countries (LMICs). In March 2017, the World Health Organization (WHO) convened a meeting to identify policies and activities to promote access to vaccination of older adults, specifically in LMICs. Participants included academic and industry researchers, funders, civil society organizations, implementers of global health interventions, and stakeholders from developing countries with adult immunization needs. These experts reviewed vaccine performance in older adults, the anticipated impact of adult vaccination programs, and the challenges and opportunities of building or strengthening an adult and older adult immunization platforms. Key conclusions of the meeting were that there is a need for discussion of new opportunities for vaccination of all adults as well as for vaccination of older adults, as reflected in the recent shift by WHO to a life-course approach to immunization; that immunization in adults should be viewed in the context of a much broader model based on an individual's abilities rather than chronological age; and that immunization beyond infancy is a global priority that can be successfully integrated with other interventions to promote healthy ageing. As WHO is looking ahead to a global Decade of Healthy Ageing starting in 2020, it will seek to define a roadmap for interdisciplinary collaborations to integrate immunization with improving access to preventive and other healthcare interventions for adults worldwide.